Identification of TRDV-TRAJ V domains in human and mouse T-cell receptor repertoires - Volkmar, Michael; Fakhr, Elham; Zens, Stefan; Bury, Alice; Offringa, Rienk; Gordon, Jessica; Huduti, Enes; Wölfel, Thomas; Wölfel, Catherine (Frontiers in Immunology, 2023)
Here we describe the identification of two T cell receptors (TR) containing TRDV genes in their TR alpha chains, the first one in human the second one in mouse. First, using 5'RACE on a mixed lymphocyte tumor-cell culture (MLTC) we identified TRDV1 5'UTR and complete coding sequence rearranged productively to TRAJ24. Single cell T cell receptor RNA sequencing of the MLTC, conducted to identify additional clonotypes, revealed that the analysis software detected the hybrid TRDV-TRAJ TR alpha chain but excluded it from the final results.In a separate project, we performed TR sequencing of tumor-infiltrating lymphocytes (TILs) in a murine tumor model. Here, the predominant clonotype contained a TR alpha chain with a TRDV2-2-TRAJ49 rearrangement. Again, the hybrid TR alpha chain was not reported in the final results.Transfection of both TR cDNAs resulted in cell surface localization of TR together with CD3 suggesting a productive protein in both cases. Tumor recognition of the Homo sapiens (Homsap) TRDV1-containing TR could be demonstrated by IFN Gamma ELISA ELISpot kit whereas the Mus musculus (Musmus) TR did not recognize a tumor-derived cell line.To determine whether the TRDV-containing TR alpha (TRA) chains we detected were rare events or whether TRDV genes are commonly incorporated into TRA chains, we queried the NCBI Sequence Read Archive for TR scRNA-seq data and analyzed 21 human and 23 murine datasets. We found that especially Homsap TRDV1, Musmus TRDV1 and to some extent Musmus TRDV2-2 are more commonly incorporated into TRA chains than several TRAV genes, making those TRDV genes a relevant contribution to TR alpha diversity.TRDV-containing TR alpha chains are currently excluded from the final results of V-(D)-J dataset analyses with the CellRanger software. We provide a workaround to avoid exclusion of those hybrid TRA chains from the final analysis results.